ECONOMIC AND SOCIAL CONDITIONS OF BLACK SOUTH AFRICANS: THE EFFECTS OF XENOPHOBIC VIOLENCE AND DEVELOPMENTAL FAILURES - Olawale , Akinola Joseph; Okoro , Ebele Chinedu (Ayden International Journal of Law, Political Science, and Administration, 2024)
The study examined how poverty and unemployment conditions of black South Africans played a part in post-apartheid xenophobic violence and crisis of development in South Africa. A qualitative research approach and explanatory research design was adopted for the study. One research question and one research hypothesis guided the study. Data was also collected through interviews, textbooks, archival materials, journals, internet, government gazettes, periodicals, newspapers, conferences and seminar papers, magazines, etcetera for the analysis of the variables under investigation. The research interview questions were content validated by an expert in the field of social research while discriminatory method was used to ascertain the reliability of the data collection instruments. Qualitative tool such as the narrative analytic technique was adopted for the data analysis. The study reports that poverty and unemployment conditions of black South Africans played a part in post-apartheid xenophobic violence and crisis of development in South Africa. The study concluded that the poverty and unemployment condition of black South African Youths is a contributory factor to xenophobic violence in South Africa. The study advocates that there is an urgent need to create policies and programmes that will address the issue of high rate of poverty and unemployment among the South African youths.